PENGARUH MOTIVASI KERJA DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. SARANA MEDIA SELULAR KABUPATEN CILACAP - Esih Jayanti; Tri Dwi Puspitasari (JURNAL EKONOMI, 2018)
The purpose of this research is to partially analyze the influence of work motivation and leadership on employee performance, to analyze simultaneusly the influence of work motivation and leadership on employee performance and to analyze the variables that have the most dominant influence on employee performance at PT. Sarana Media Selular Cilacap. The sample used is 30 people consisting of admin, sales, cashier and front liner. The research instrument used questionnaires, which were arranged on a scale of 1-5, score 1 for very dissatisfied responses and a score of 5 for responses strongly agreed. Data analysis technique used is descriptive analysis and multiple regression analysis. To know the magnitude of the influence oh motivation and leadership on the performance of employees in PT. Sarana Media Selular of Cilacap Regency used multiple linear regression analysis. To test the effect simultaneously used F-tes with degrees of freedom (df) = k and (n-k-2) with a confidence level of 5% (Î±=0,05). Pursuant to result of T test of work motivation variable got value tcount>ttable that is 2,361 > 2,048 hypothesis accepted. Job satisfaction variable obtained by tcount>ttable is 2,087 > 2,048 hypothesis accepted. The result of the analysis is Fcount>Ftable that is 23,381 > 3,328. Based on the results of research the most dominant variables affect the performance of employees in PT. Sarana Media Selular of Cilacap that is motivation with beta coefficient of 0,447 is greater than leadership of 0,395. The value of coefficient of determination adjusted Rsquare equal to 72,7% performance variable of employees can be explained by motivation and leadership variable, while 36,6% is explained by other variable outside this research. Keywords: motivation work, leadership, performance of employees.